The Role of Interactive Technologies in the Development of Communicative Competence - Mashkhura Anvarjon kizi Saydaliyeva (Researchparks Publishing, 2022)
This article presents a theoretical study of research problems, reveals the essence of the basic concepts. Interactive learning technologies are seen as an effective tool of development of communicative competence of students. Interactive training - is primarily a dialog learning, in which the interaction is not only teachers and students but also trainees together. There are several features of interactive teaching technologies that allow them to use them effectively in the learning process: the organization of the process of acquiring new experiences and exchanges are available; the ability to maximize the use of each student's personal experience. The following methods were used in the study: Theory: analysis of philosophical, psychological, pedagogical and methodological, linguistic literature; modeling; generalization of high school teachers' pedagogical experience; empirical: observational - direct, indirect, and participant observation; study of educational activity of product students; diagnostic, questionnaires, interviews, tests; experimental, mathematical statistics methods, systemic and qualitative analysis of experimental data and their graphic interpretation . The study's findings demonstrated the efficacy of interactive technology in English language instruction.